Crafting New Business Strategy In Indonesia's Fertilizer Company ( Case Study in PT XYZ) - Faswara, Lufan Nassya; Toha, Mohamad (The Indonesian Journal of Business Administration, 2012)
Fertilizer is the important product in Indonesia. The growth of Indonesia’s is highly depending on the supply of fertilizer. PT XYZ is one of the national fertilizer company in Indonesia. PT XYZ is a subsidiary company of a State Owned Enterprise (BUMN) in Indonesia which engaged in fertilizer production and distribution. PT XYZ is the first fertilizer company in Indonesia with objectives to supply fertilizer products to Indonesian farmers. This time, PT XYZ is facing problems in achieving its sales target, having old plant facilities, and sourcing of natural. Those problems are the overcome challenges of the company in the future. In accordance with those problems, this final project will craft PT XYZ’s business strategy and its implementation plan to overcome future challenges.To craft the business strategies, business situations were explored externally and internally. External opportunities & threats and internal strengths & weaknesses are the main factors to formulate the business strategy. Those business situations are described in the SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis. SWOT analysis is determining strategic positioning to formulate company’s business strategy. Business strategy formulation is conducted with using TOWS Matrix and Business Model Analysis tools. The strategic implementation plan has developed based on strategic formulation and the availability of the company.The result of analysis toward the information that is obtained from PT XYZ, it concludes that PT XYZ’s business strategy is based on cost leadership strategic positioning. Those proposed business strategies are conducting fertilizer plant revitalization, conducting of coal gasification system, increasing non subsidized fertilizer sales, and developing business area to Tj. Api-Api.The implementation plan of those strategies is suggested on action plant that adjusted with related functions in the company. Strategic implementation will be implemented in the next 4 years and will start in 2012.Keywords: Fertilizer Industry, Business Strategy, Business Model Analysis